Feeding the People, Feeding the Spirit: Revitalizing Northwest Coastal Indian Food - Anderson, E. N. (Ethnobiology Letters, 2011)
Review of Feeding the People, Feeding the Spirit: Revitalizing Northwest Coastal Indian Food. Elise Krohn and Valerie Segrest. 2010. Northwest Indian College, Bellingham, WA. Pp. x + 158, copiously illustrated, tables, bibliography.